Regional Leptomeningeal Score on CT Angiography Predicts Clinical and Imaging Outcomes in Patients with Acute Anterior Circulation Occlusions - Menon, B.K.; Smith, E.E.; Modi, J.; Patel, S.K.; Bhatia, R.; Watson, T.W.J.; Hill, M.D.; Demchuk, A.M.; Goyal, M. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: The regional leptomeningeal score is a strong and reliable imaging predictor of good clinical outcomes in acute anterior circulation ischemic strokes and can therefore be used for imaging based patient selection. Efforts to determine biological determinants of collateral status are needed if techniques to alter collateral behavior and extend time windows are to succeed. MATERIALS AND METHODS: This was a retrospective Institutional Review Board–approved study of patients with acute ischemic stroke and M1 middle cerebral artery+/− intracranial internal carotid artery occlusion at our center from 2003 to 2009. The rLMC score is based on scoring pial and lenticulostriate arteries (0, no; 1, less; 2, equal or more prominent compared with matching region in opposite hemisphere) in 6 ASPECTS regions (M1–6) plus anterior cerebral artery region and basal ganglia. Pial arteries in the Sylvian sulcus are scored 0, 2, or 4. Good clinical outcome was defined as mRS ≤2 at 90 days. RESULTS: The analysis included 138 patients: 37.6% had a good (17–20), 40.5% a medium (11–16), and 21.7% a poor (0–10) rLMC score. Interrater reliability was high, with an intraclass correlation coefficient of 0.87 (95% CI, 0.77%–0.95%). On univariate analysis, no single vascular risk factor was associated with the presence of poor rLMCs (P ≥ .20 for all comparisons). In multivariable analysis, the rLMC score (good versus poor: OR, 16.7; 95% CI, 2.9%–97.4%; medium versus poor: OR, 9.2, 95% CI, 1.7%–50.6%), age (<80 years), baseline ASPECTS (≥8), and clot burden score (≥8) were independent predictors of good clinical outcome. CONCLUSIONS: The rLMC score is a strong imaging parameter on CT angiography for predicting clinical outcomes in patients with acute ischemic strokes. ACAanterior cerebral arteryASPECTSAlberta Stroke Program Early CT ScoreCIconfidence intervalCLconfidence limitCTACT angiographyCTAsiCT angiography source image(s)DSAdigital subtraction angiographyIAintra-arterialICAinternal carotid arteryIQRinterquartile rangeIVintravenousMCAmiddle cerebral arterymRSmodified Rankin ScaleNCCTnoncontrast CTNIHSSNational Institutes of Health Stroke Scale scoreORodds ratioPCAposterior cerebral arteryrLMCregional leptomeningeal collateralTIAtransient ischemic attackTOASTTrial of Org 10172 in Acute Stroke TreatmenttPAtissue plasminogen activator